2006
DOI: 10.1074/jbc.m600861200
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin-3-glucoside, a Natural Product Derived from Blackberry, Exhibits Chemopreventive and Chemotherapeutic Activity

Abstract: Epidemiological data suggest that consumption of fruits and vegetables has been associated with a lower incidence of cancer. Cyanidin-3-glucoside (C3G), a compound found in blackberry and other food products, was shown to possess chemopreventive and chemotherapeutic activity in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
190
2
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(206 citation statements)
references
References 50 publications
6
190
2
8
Order By: Relevance
“…Ding et al (2006) reported that cyanidin-3-glucoside inhibited proliferation of A549 human lung carcinoma cells. Proliferation of A549 cells was completely blocked by purified (99% purity) at a concentration of 40 μmol/L for 72 h. Zhang et al (2005) only reported different effects for cyanidin and cyanidin-3-glucoside in MCF-7 human breast cancer cells among the cells they tested.…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al (2006) reported that cyanidin-3-glucoside inhibited proliferation of A549 human lung carcinoma cells. Proliferation of A549 cells was completely blocked by purified (99% purity) at a concentration of 40 μmol/L for 72 h. Zhang et al (2005) only reported different effects for cyanidin and cyanidin-3-glucoside in MCF-7 human breast cancer cells among the cells they tested.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanidin-3-glucoside belongs to the flavonoid class of molecules and is a member of the anthocyanin family, the largest group of pigments present in many edible berries, dark grapes, cabbages, and other pigmented foods (Ding et al 2006;Ozgen et al 2009a, b). The stability of anthocyanins during thermal processing has been well documented by several researchers (Scalzo et al 2008;Kirca et al 2007;Wang and Xu 2007).…”
Section: Total Anthocyanins Contentmentioning
confidence: 99%
“…Extratos de amora-preta têm apresentado efeito anti-mutagênico (TATE et al, 2006) e anticarcinogênico em linhagens humanas de câncer de útero, câncer de cólon (LAZZE et al, 2004), câncer oral, câncer de mama, câncer de próstata (SEERAM et al, 2006) e câncer de pulmão (DING et al, 2006). Segundo Tate et al (2004), extratos de amora-preta podem prevenir a formação de metastase.…”
Section: Fitoquímicosunclassified
“…Em ratos, antocianinas extraídas de amora-preta foram capazes de reduzir o número e o tamanho de tumores (câncer de pele) malignos e não malignos, os quais foram induzidos quimicamente na pele destes animais. Estes compostos inibiram a migração e invasão do câncer (DING et al, 2006).…”
Section: Fitoquímicosunclassified